2016
DOI: 10.17235/reed.2016.4488/2016
|View full text |Cite
|
Sign up to set email alerts
|

Peroral endoscopic myotomy versus pneumatic dilation for achalasia in patients aged = 65 years

Abstract: Background and aim: Both peroral endoscopic myotomy (POEM) and pneumatic dilation (PD) has proved to be effective for treating achalasia in patients aged ≥ 65 years. However little is known about the comparison between POEM and PD. The aim of the study was to compare the safety and efficacy of POEM and PD for the treatment of achalasia in these patients.Methods: We retrospectively reviewed the medical records of patients aged 65 years-old or more who received POEM or PD for the treatment of achalasia at our ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 30 publications
2
25
0
Order By: Relevance
“…In the elderly, on account of associated diseases, endoscopic treatment is used as the first line. The clinical success rate in our study for this subgroup was similar to the overall success rate [20,21].…”
Section: Discussionsupporting
confidence: 83%
“…In the elderly, on account of associated diseases, endoscopic treatment is used as the first line. The clinical success rate in our study for this subgroup was similar to the overall success rate [20,21].…”
Section: Discussionsupporting
confidence: 83%
“…748 records were screened, and 88 full-length articles were assessed. Sixty-six studies were included in the final analysis, four of which directly compared outcomes of POEM to PD [32,35,36,38] [35, 40, 68, 78, 79, 83 ,89]. Of the 66 included studies, 62 were cohort studies (30 retrospective and 32 prospective), three case series and one randomized controlled trial.…”
Section: Search Results and Population Characteristicsmentioning
confidence: 99%
“…The detailed assessment of study quality can be found in Supplementary Table 4. Overall, three studies [32,36,38] were considered high quality and the rest [12, 24-34, 36-42, 44, 46-56, 58-91] were considered of medium quality. There were no low-quality studies.…”
Section: Quality Of Included Studiesmentioning
confidence: 99%
“…Wang et al . compared the efficacy of POEM and pneumatic balloon dilatation in patients older than 65 years . In this group, the efficacy of these two procedures was 92.2% and 80.0% (success defined as an ES of ≤3), respectively, without any major complications …”
Section: Clinical Questions and Statementsmentioning
confidence: 99%